2017
DOI: 10.21276/ijrdpl.2278-0238.2017.6(5).2748-2756
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity study of Mesenchymal Stromal cells derived from Wharton’s Jelly in mouse by intravenous and subcutaneous route

Abstract: Available online on:15.08.2017@http://ijrdpl.com http://dx.doi.org/10.21276/IJRDPL.227 8-0238.2017.6(5).2748-2756 ABSTRACT:Aim: The present study was to evaluate the acute toxicity of WJ-MSCs in mouse by intravenous and subcutaneous route and to assess their potential for side effects, MLD, MTD and LD 50 . Objectives: Wide ranges of clinical and preclinical trials have suggested exploitation of adult MSCs for the cell-based reparative therapeutic approach; considering pros and cons of embryonic stem cells. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…As far as we know, this present study is the first to demonstrate that IV administration of hUC-MSCs of up to 40 × 10 6 cells/kg BW in a single dose did not cause clinical sign of toxicity and tumorigenicity in acute, sub-chronic and tumorigenicity studies in healthy BALB/c and immunocompromised B-NDG mice and is the maximum tolerable dose. Similar outcomes have been previously reported with lower doses of hUC-MSCs up to 10 × 10 6 cells/kg BW in a single injection were also safe (Wang et al 2012 ; Kannaiyan et al 2017 ; Chan et al 2022 ; Xu et al 2022 ; Pan et al 2023 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As far as we know, this present study is the first to demonstrate that IV administration of hUC-MSCs of up to 40 × 10 6 cells/kg BW in a single dose did not cause clinical sign of toxicity and tumorigenicity in acute, sub-chronic and tumorigenicity studies in healthy BALB/c and immunocompromised B-NDG mice and is the maximum tolerable dose. Similar outcomes have been previously reported with lower doses of hUC-MSCs up to 10 × 10 6 cells/kg BW in a single injection were also safe (Wang et al 2012 ; Kannaiyan et al 2017 ; Chan et al 2022 ; Xu et al 2022 ; Pan et al 2023 ).…”
Section: Discussionsupporting
confidence: 81%
“…Several animal toxicology studies have been conducted to evaluate the efficacy and safety of MSCs from predominantly bone marrow sources (Rengasamy et al 2016 ; Tayebi et al 2022 ). Safety, toxicity and tumorigenicity studies looking at hUC-MSCs were more limited (Wang et al 2012 ; Kannaiyan et al 2017 ; Chan et al 2022 ; Xu et al 2022 ; Pan et al 2023 ). Chan and co-workers reported that hUC-MSCs infused at a dose of 10 × 10 6 cells/kg BW intravenously on Sprague Dawley rats were considered safe and did not alter the haematological and biochemical as well as histological parameters in animals within the 12-wk study (Chan et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%